Mechanistic Studies on Photoacylation - Megawati Santoso (Jurnal Matematika & Sains, 1997)
An unprecedented photoacylation method for preparation of acyl- and aroyliron(III) porphyrin complexes has been reported1). This paper present the mechanistic studies on such photoacylation. Detailed mechanistic studies on the photoacylation of chloroiron(III) tetraphenylporphyrin ((TPP)FeCl) suggest "controlled" radical reactions. In the presence of UV light (TPP)FeCl undergoes intramolecular electron transfer to yield (TPP)Fe(II) and chlorine radical. Aldehyde prevents the back electron transfer by trapping the chlorine radical to form the corresponding acyl radical. The photoreduced (TPP)Fe(II) then undergoes oxidative addition with the acyl radical to yield the corresponding acyliron(III) tetraphenylporphyrin complex.